2014
DOI: 10.1071/ah14049
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 'rehabilitation in the home' service

Abstract: Objectives. Rehabilitation in the home (RITH) services increasingly provide hospital substitution services. This study examines clinical outcomes in a large metropolitan RITH service in Western Australia.Methods. The 2010 database of Fremantle Hospital RITH service was interrogated to identify the clinical profile of cases, length of stay (LOS) and clinical outcomes. Negative outcomes included death or unexpected hospital readmission. Multiple logistic regression modelling was used to explore associations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
(18 reference statements)
1
14
1
Order By: Relevance
“…The value of home health services may vary by country. Rehabilitation in the home environment has proven cost effective in Western Australia for multiple conditions, including elective joint surgery, improving quality of life with reduced rates of mortality [42]. Conversely, although home PT was as effective and as acceptable to TKA patients undergoing outpatient hospital PT, it was more costly than treatment in the facility [43].…”
Section: Discussionmentioning
confidence: 95%
“…The value of home health services may vary by country. Rehabilitation in the home environment has proven cost effective in Western Australia for multiple conditions, including elective joint surgery, improving quality of life with reduced rates of mortality [42]. Conversely, although home PT was as effective and as acceptable to TKA patients undergoing outpatient hospital PT, it was more costly than treatment in the facility [43].…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have not described their patients in similar detail for direct comparison, however. 10,[15][16][17] Three-months after discharge, patients had improved functional independence and mobility compared to their home-based rehabilitation admission status but did not return to preadmission levels. This contrasts a study of similarly aged acutely hospitalized patients, which found comparable rates of ADL and IADL independence at hospital admission and three-months postdischarge.…”
Section: Discussionmentioning
confidence: 99%
“… 16 A retrospective chart review of home‐based rehabilitation patients (no age criteria, 70.6% aged ≥65 years) found that negative outcomes of hospital ward readmission or death occurred more frequently in older adults compared to younger adults. 17 However, this study did not report mobility, physical performance, or postdischarge outcomes, which are important considerations when evaluating hospital care for geriatric inpatients. 18 One retrospective study of a home‐based postacute rehabilitation service (mean age 84.2 years), found that most patients achieved their mobility goals and improved global function, and the authors provide a detailed description of the multidisciplinary care model.…”
Section: Introductionmentioning
confidence: 95%
“…There is evidence of improved outcomes from home‐based rehabilitation care in a geriatric patient cohort compared to hospital‐based care, including lower odds of developing delirium, fewer hospital bed days and greater satisfaction regarding rehabilitation quality 2 . Similar positive results have been shown following orthopaedic surgery 3 and in several large trials following stroke, 4 with a low rate of negative outcomes being seen with home‐based rehabilitation care in a recent Western Australian study 5 . The concept of home‐based rehabilitation was also supported by the recent Travis Review of Victorian hospital capacity published in 2015 6 .…”
Section: Introductionmentioning
confidence: 79%
“…2 Similar positive results have been shown following orthopaedic surgery 3 and in several large trials following stroke, 4 with a low rate of negative outcomes being seen with home-based rehabilitation care in a recent Western Australian study. 5 The concept of home-based rehabilitation was also supported by the recent Travis Review of Victorian hospital capacity published in 2015. 6 This review recommended an expansion of home-based care options due to 'The potential benefits in patient outcomes and cost-effectiveness support further development of these models across the system (P10)'.…”
Section: Introductionmentioning
confidence: 98%